The Automatic Packaging Machinery Sector in Italy and Germany - Fortis, Marco (Springer, 2015)
This book analyzes the wrapping and packaging machinery sector in the Emilia/Bologna district in Italy and compares the most recent trends with those in the industry in Schwäbisch Hall and Waiblingen, Baden-Württemberg, Germany, which represents a direct rival. In a detailed and original study, the authors trace the evolution of manufacturing in Bologna during a period that witnessed extraordinary growth in automatic wrapping and packaging machines, leading the sector to become a central pillar of Italian mechanical engineering. Similarly, the history of the industry in the Emilia district is described, highlighting the factors that led to its success. A comprehensive comparative analysis of the German and Italian sectors is then performed. Export figures and the trade balance for the sector are examined based on Eurostat data, and the significance of the two districts in terms of global trade is identified with reference to UN data. In addition, the number of companies, sales, and the size of the workforces are thoroughly compared. The book will be of interest to economists and others with an interest in the development and importance of the automatic packaging machinery sector.